CORRELATION BETWEEN PLASMA CONCENTRATION OF A NEW CEFTIOFUR FORMULATION AND MINIMUM INHIBITORY CONCENTRATION VALUES OF ZOOTECHNICAL INTEREST MICROORGANISMS IN CATTLE AND PIGS. - FECHIS, A. D. S.; MARCHIORI FILHO, M.; LEONELO NETO, A.; BRUNINI, M.; OKADA, R. A. R.; DAMIÃO NETO, C. F.; SOSSAI, S. (Ars Veterinaria, 2024)
Ceftiofur is a third-generation cephalosporin widely used in cattle and swine farming to treat respiratory and reproductive conditions. The veterinary pharma industry consistently develops new formulations with this molecule to bring highly effective products to market with short withdrawal periods, ensuring consumer safety for products derived from treated animals. The study aimed to evaluate the plasma concentration profile of Vilocci, a new formulation of ceftiofur, in comparison to the minimum inhibitory concentrations (MIC) of various pathogens commonly found in bovine and swine farming. Ten animals from each species were used, and a single dose of 1 mg/kg was given to bovines and 5 mg/kg to swine. Blood samples were collected at 12 time points to construct the pharmacokinetic profile. The minimum inhibitory concentration (MIC) of growth for the pathogens of interest isolated from the target species was determined and the effectiveness of the for; mulation was assessed for each one.